The implementation of spiritual education program among the Malaysian Armed Forces personnel. - Jalal, Burhanuddin; Abdul Rahman, Zainurin; Sheikh Ahmad, Ismail; Madarsha, Kamal Basha; Othman, Joharry; Nordin, Mohamad Sahari; , (Human Resource Management Academic Research Society (HRMARS), 2017)
The strength of the military organization can be measured through three important elements which are the firing power, mobility power and combat power. The aspect of the fighting spirit encompasses the aspect of the spiritual readiness, a fundamental element that needs to be consolidated within all Malaysian Armed Forces personnel's. It has to stay at the top level and they have to be constantly ready in defending the sovereignty of the state. The readiness of the military institutions is not only assessed in terms of asset equipment and sophisticated tools, but even more important, is the spiritual value within every military member, especially in terms of self-readiness to shoulder the responsibility and mandate of the country. In this matter, KAGAT or Kor Agama Angkatan Tentera Malaysia (Malaysian Armed Forces Religious Corps), through the Malaysian Armed Forces Islamic Spirituality and Mental Construction Policy , which has covered various Islamic education and spiritual activity programs to every layer of the MAF organization, has introduced a spiritual education program for personnel's of the Malaysian Armed Forces (MAF). The focus of the study is to make an early assessment on the program implementation from the aspect of planning, implementation and also monitoring through the perspectives of the MAF personnel's. The study methodology involves the mixedmethod, namely the qualitative and the quantitative methods and 1,137 respondents had been involved. The study findings also show that there is a close relationship in terms of the environment, benefit, teacher and the preacher (members of KAGAT), and also the members' attitude towards the program. The study findings also show that spiritual strength has a positive relationship towards the readiness and the fighting strength of the Malaysia Armed Forces. Indeed, the Islamic education also dacwah efforts carried out by the Malaysian Armed Forces Religious Corps should further be strengthened so that the spiritual readiness of the Malaysian Armed Forces personnel's gets to be increased to ensure that they always fulfil two main aspects concerned- the combat power as the physical aspect and the spirituality so we shall have a credible line of quality and excellent soldiers. The impact of this research will strengthen the opinion that the basic Islamic education is a platform launcher for Malaysian Armed Forces Religious Corps to intensify the efforts of religious education systematically and efficiently.